Employee organisational commitment and the mediating role of work locus of control and employee job satisfaction: The perspective of SME workers - Miston Mapuranga; Eugine Tafadzwa Maziriri; Tarisai Fritz Rukuni; Thobekani Lose (Journal of Risk and Financial Management, 2021)
In Southern Africa, employees play a critical role in the growth of small and medium enterprises (SMEs). As a result, SMEs' effectiveness depends on the presence of virtuous workplace spirituality and procedural justice, which affects work locus of control, employee job satisfaction, and employee organisational commitment. The researchers looked at how work locus of control, employee job satisfaction, and employee organisational commitment were influenced by workplace spirituality and procedural justice among SME employees in Harare, Zimbabwe. The study data was quantitatively analysed. According to the results, workplace spirituality, procedural justice, and work locus of control all play a role in enhancing employee job satisfaction and commitment. The relationship between workplace spirituality, procedural justice, and employee organisational commitment was positively influenced by work locus of control and employee job satisfaction. The findings of this study are expected to provide valuable insights into the unique key determinants affecting work locus of control, employee job satisfaction, and employee commitment to the organisation.
Keywords: 330; employee job satisfaction; employee organisational commitment; procedural justice; work locus of control; workplace spirituality